Pembangunan IKN dalam perspektif aksiologi: Penilaian etik terhadap penggalian dan penerapan ilmu - Nabila, Siti (Maliki Interdisciplinary Journal, 2026)
The development of Indonesia’s new capital, Nusantara (IKN), marks a major transformation in the country’s geopolitical landscape and spatial planning. This study examines the IKN project through the lens of axiology, focusing on the ethical and value-based dimensions of knowledge production and application. Using a qualitative-descriptive approach, the article analyzes the extent to which moral considerations are taken into account in scientific decision-making, particularly regarding environmental impact, the relocation of Indigenous communities, and the use of technology. The findings indicate that a technocratic approach tends to dominate, potentially overlooking principles of social justice and ecological sustainability. Therefore, a systematic integration of axiological reflection into development policies is essential to ensure that IKN serves not only as a symbol of modernity but also as an embodiment of the ethical responsibility of science within the context of national development.